Analisis Pengaruh Work Life Balance Dan Burnout Terhadap Kepuasan Kerja Pada Bank Muamalat Indonesia KC Medan Balai Kota - Nur Hasanah; Imsar Imsar; Juliana Nasution (Manajemen dan Bisnis, 2023)
The purpose of this study was to analyze whether there is an effect of work life balance and burnout on job satisfaction among Bank Muamalat Indonesia KC Medan Balai Kota employees, the object of this study were all 30 employees at Bank Muamalat KC Medan Balai Kota, using quantitative research methods. The results of this study indicate that there is a significant influence between work life balance on employee job satisfaction at Bank Muamalat Indonesia KC Medan Balai Kota. Prove that the value of F count is 12.516 F table 3.34. In the partial test (t), the work life balance variable has a positive and significant effect on employee job satisfaction, this is evidenced by the results of t count t table (3.888 2.051). The Burnout variable has a negative and insignificant effect on employee job satisfaction, this is evidenced by t count t table, namely (-1.082 2.051). The results of the coefficient of determination test showed that 48.1% of job satisfaction (Y) was influenced by the variables work life balance (X1) and burnout (X2), while the rest were influenced by other variables that were not examined in this study.